Evaluasi kinerja bidan dalam pelayanan antenatal menggunakan pendekatan balanced scorecard Di kabupaten banjar & kabupaten barito kuala Tahun 2016 - rapidah rapidah; rusmilawaty rusmilawaty (Jurnal Skala Kesehatan, 2019)
Number of infant deaths in South Kalimantan Province in 2015 was still quite high at 515 people, at the district / city level , Banjar Regency ranks first in the number of infant deaths by 64 cases, North Hulu Sungai Regency by 61 cases, South Hulu Sungai Regency by 60 cases and Barito Kuala District by 58 cases. The number of midwives has been relatively scattered throughout the South Kalimantan region, but has not been able to reduce the number of infant deaths, especially in the Banjar and Barito Kuala Regencies. Evaluation needs to be done on the performance of antenatal services, in order to get an overview of antenatal services comprehensively, it can use a measuring tool, namely the balanced scorecard. This study aims to describe the performance evaluation of midwives inservices antenatal care including financial perspectives, internal business perspectives, perspectives The design of this study was a descriptive approach. Instruments using balanced scorecard. The sample was 156 pregnant women, 3 Puskesmas heads and 3 midwives coordinators at Karang Intan Public Health Center Anjir Pasar and Anjir Muara Financial perspective in the form of operational funds for antenatal services sourced from BOK funds (Health Operational Assistance), internal business process perspective showed most of the respondents who did antenatal visits / examinations received services according to the 10 T standard of 83 people (53.3%), customer perspectives showed that most respondents who did antenatal visits / examinations were not satisfied with the services provided by 87 people (55.8 %), growth and human resource perspectives obtained by midwife education as much as 2 people (67%) with a Diploma IV Midwifery background and 1 person (33%) with a Midwifery Diploma III background. Keywords: Performance, Balanced Score Card